Water transport through tall trees: A vertically explicit, analytical model of xylem hydraulic conductance in stems. (8th June 2018) - Couvreur, Valentin; Ledder, Glenn; Manzoni, Stefano; Way, Danielle A.; Muller, Erik B.; Russo, Sabrina E.
Abstract: Trees grow by vertically extending their stems, so accurate stem hydraulic models are fundamental to understanding the hydraulic challenges faced by tall trees. Using a literature survey, we showed that many tree species exhibit continuous vertical variation in hydraulic traits. To examine the effects of this variation on hydraulic function, we developed a spatially explicit, analytical water transport model for stems. Our model allows Huber ratio, stem‐saturated conductivity, pressure at 50% loss of conductivity, leaf area, and transpiration rate to vary continuously along the hydraulic path. Predictions from our model differ from a matric flux potential model parameterized with uniform traits. Analyses show that cavitation is a whole‐stem emergent property resulting from non‐linear pressure‐conductivity feedbacks that, with gravity, cause impaired water transport to accumulate along the path. Because of the compounding effects of vertical trait variation on hydraulic function, growing proportionally more sapwood and building tapered xylem with height, as well as reducing xylem vulnerability only at branch tips while maintaining transport capacity at the stem base, can compensate for these effects. We therefore conclude that the adaptive significance of vertical variation in stem hydraulic traits is to allow trees to grow tall and tolerate operating near their hydraulic limits. Abstract : Understanding the hydraulic challenges faced by tall trees requires accurate stem hydraulic models. We developed a spatially explicit, analytical water transport model for stems that allows for vertical variation in intrinsic and extrinsic hydraulic traits, incorporates gravity and vertical variation in transpiration, and predicts pressure, conductivity, and cavitation at any point on the stem hydraulic path. We found that our vertically explicit model made different predictions of hydraulic function compared with a matric flux potential model due to the compounding effects of vertical trait variation and gravity with tree height. Growing proportionally more sapwood and building xylem tapered with height, as well as reducing xylem vulnerability only at branch tips while maintaining transport capacity at the stem base, can compensate for these effects and allow trees to grow tall and tolerate operating near their hydraulic limits.